Synthesis of the C1–C9, C11–C19 Pyran Core and C19–C24 Fragments of Macrolactin 3 - Maheshwar Reddy, A.; Sabitha, Gowravaram (SynOpen, 2017)
We describe herein an efficient synthesis of the C1–C9, C11–C19 pyran moiety and C18–C24 core fragments of macrolactin 3. The prominent features of this work include construction of the Z-double bond of the 1,3-(Z,E)-diene system utilizing Horner–Wadsworth–Emmons reaction under Still–Gennari conditions. A Sharpless asymmetric epoxidation and subsequent epoxide opening under BF3·OEt2 conditions were applied to generate the stereogenic centers at C15 and C16, oxa-Michael addition and Jacobsen resolution facilitate the synthesis of the fragments.
Keywords: macrolactin 3; tetrahydropyran; BF3·OEt2; epoxide opening; Jacobsen; oxa-Michael; d-ribose